XBRL adoption and asset impairment decision: role of audit effort - Dalci, Ilhan (Emerald Group Publishing Ltd, 2025)
PurposeThis study aims to explore how mandatory and voluntary adoption of eXtensible Business Reporting Language (XBRL) influences asset impairment decisions. This study also investigates the moderating role of audit effort on the association between XBRL adoption and asset impairment decisions.Design/methodology/approachThis study uses 1,288 listed firms with 24,472 firm-year observations from the UK, which uses International Financial Reporting Standards and implements XBRL mandatorily. In addition, it uses a sample of 1,627 listed firms with 30,913 firm-year observations from Australia, which also uses International Financial Reporting Standards but implements XBRL voluntarily. The financial data used in this study is downloaded from LSEG Workspace Database, and logistic regression is used to test the research hypotheses. In addition, the Difference in Difference method is used to tackle the potential endogeneity issue.FindingsThe results reveal that both mandatory and voluntary adoption of XBRL increases the likelihood of reporting asset impairments. The results also indicate that audit effort positively moderates the association between XBRL adoption and asset impairment decision. Moreover, the results of the Difference in Difference analysis imply that adoption of XBRL increases the likelihood of reporting asset impairments even for voluntary XBRL adopters.Research limitations/implicationsThis study provides several contributions and implications. First, the main theoretical contribution of this study is that XBRL, as a new technology for financial reporting, influences asset impairment decisions. The other theoretical contribution of this study indicates that audit effort improves the positive influence of XBRL adoption on asset impairment decisions. Second, by considering asset impairment tests as an important mechanism of conditional conservatism, which is a key aspect of accounting quality (Andr & eacute; et al., 2015), the results are expected to assist investors and creditors by providing them with a practical implication that the adoption of XBRL improves accounting quality through asset impairments. This is expected to enhance the quality of decisions made by investors and creditors. Third, this study provides additional evidence on the positive consequences of XBRL adoption with respect to financial reporting. Therefore, the results are expected to assist regulators which consider mandating the use of XBRL in their countries in evaluating its potential benefits.Originality/valueTo the best of the author's knowledge, this study is the first attempt to investigate the association between XBRL adoption and asset impairment decisions. Considering asset impairments as a reflection of accounting quality, the significance of asset impairments for investors and creditors (Sundkvist and Stenheim, 2022) and the increasing number of companies using XBRL (Lai et al., 2015), the results provided by this study are valuable.
Keywords: XBRL; Asset impairment; Impairment decision; Audit effort; Audit fees